2020
DOI: 10.1017/s0950268820001818
|View full text |Cite
|
Sign up to set email alerts
|

Increasing molecular diagnostic capacity and COVID-19 incidence in Brazil

Abstract: Different countries have adopted strategies for the early detection of SARS-CoV-2 since the declaration of community transmission by the World Health Organization (WHO) and timely diagnosis has been considered one of the major obstacles for surveillance and healthcare. Here, we report the increase of the number of laboratories to COVID-19 diagnosis in Brazil. Our results demonstrate an increase and decentralisation of certified laboratories, which does not match the much higher increase in the number of COVID-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…This group daily catches, from the epidemiological reports of each state, the number of confirmed cases and death by SARS-CoV-2 and make it publicly available. Because of the recognition of SARS-CoV-2 as a pandemic by the WHO, laboratory certification in Brazil ranged from few laboratories to 26, in eight weeks since the beginning of the epidemic; the majority is located at São Paulo State [ 14 ]. Data reporting of Severe Acute Respiratory Illness (SARI) is mandatory in Brazil.…”
Section: Methodsmentioning
confidence: 99%
“…This group daily catches, from the epidemiological reports of each state, the number of confirmed cases and death by SARS-CoV-2 and make it publicly available. Because of the recognition of SARS-CoV-2 as a pandemic by the WHO, laboratory certification in Brazil ranged from few laboratories to 26, in eight weeks since the beginning of the epidemic; the majority is located at São Paulo State [ 14 ]. Data reporting of Severe Acute Respiratory Illness (SARI) is mandatory in Brazil.…”
Section: Methodsmentioning
confidence: 99%
“…Araquara and Barretos). Grotto et al [ 5 ] showed that molecular diagnosis increased in São Paulo State over the epidemiological weeks, but it does not match the much higher increase in the number of cases, challenging diagnostic capacity and, therefore, accurate and timely health surveillance.…”
Section: Resultsmentioning
confidence: 99%
“…We aimed to study COVID-19 advance in all these regions by analysing new confirmed cases per day (after the first case of COVID-19 in Brazil) and calculating the effective reproduction number ( R t ) of SARS-CoV-2 over time. Also, daily new cases of Severe Acute Respiratory Illness (SARI) and its R t number were estimated as an alternative way to follow the temporal evolution of the disease in a country still struggling to increase testing capacity [ 5 ].…”
Section: Background and Epidemiologymentioning
confidence: 99%
“…It comprises all severe hospitalized cases related to respiratory viruses whose notification is compulsory in Brazil. It has been a good thermometer to catch the disease spatiotemporal dynamics in the country, since it has struggled with an insufficient capacity of molecular diagnosis and fast tests 21 . The information available does not distinguish between imported and autochthonous cases.…”
Section: Reported Casesmentioning
confidence: 99%